Frequency Of Burnout Among Healthcare Professionals In A Tertiary Care Hospital, After The COVID-19 Pandemic - Yasira Abbasi; Lubna Meraj; Asma Batool; Samreena Mansoor; Sidra tul Muntaha; Anjum Jalal (Journal of Rawalpindi Medical College)
Objective: In this study, we plan to estimate the frequency of burnout among healthcare providers in a specialized teaching Hospital.